Learning organization practices : a profile of SKF Bearing Industries (Malaysia) Sdn. Bhd. - Daramy, Amadu (1998)
Learning organization (LO) paradigm is now one of the most contemporaneous issues in management practices. However, the LO concept and its impact on strategic management research and practice still remains unclear and under-examined in Malaysia. Empirical studies intended to help managers implement the learning organization concept is hardly found. This research project attempts to redress these problems by examining the extent to which SKF Bearing Industries (M) Sdn. Bhd. is transforming itself into a learning organization using a model developed by Marquardt. (1996). The specific objectives were to: 1) identify different levels, types, and skills of learning practices in the organization; 2) identify method of empowerment of the people involved with the organization in terms of learning; 3) identify process of knowledge acquisition, creation, storage transfer and utilization in the organization; 4) identify the use of technology in term of access to and exchange of information and learning in the organization; and 5) identify the organizational setting and body in which learning occurs. Twenty six (26) respondents in all were interviewed; 2] on self administered questionnaire and 5 top managers on open interview using a tape recorder. Descriptive research approach employing mainly a quantitative method which was considered appropriate was utilized for this study. Respondents were asked to rate 10 statements for each of the five (5) variables in the model on a four point likert type scale, the extent to which it applies to their organization. The variables involved were learning, organization, people, knowledge and technology. The findings of the study showed that SKF Bearing Industries (M) Sdn. Bhd. is yet in a moderate stage of becoming a learning organization. It was clear from the respondents that SKF is committed to support continuous learning of its staff through numerous training efforts and has strongly embarked on Total Quality Management efforts to drive changes within the organization. It was also clear that SKF engenders internal learning structures and inspires and fosters learning. Decentralization, delegation of authority and sharing of knowledge with customers seemed to be highly emphasized. Knowledge management seems to be on a divergent thoughts. However people empowerment and technology application were revealed to be weak.